SIMON’S HYSTERIA IN JULIA QUINN’S BRIDGERTON: THE DUKE AND I: Hysteria, Symptoms, Causes, Impacts - Emira Benaya Fatharani; Danu Wahyono (Fakultas Sastra Universitas Gresik, 2022)
This research is an analysis that discusses the hysteria experienced by Simon, one of the main characters in the Julia Quinn’s Bridgerton: The Duke and I. The discussion is divided into four parts, namely how the symptoms of hysteria are, what are the causes of hysteria, how is the impact of hysteria, and how Simon deals with his hysteria. In conducting this analysis, psychoanalytic theory is applied as a literary approach that focuses on Sigmund Freud's Theory of Hysteria. This theory serves as a reference in conducting this research. The results of the analysis which showed that Simon experienced hysteria made Simon experience several symptoms, such as symptoms of Reminiscence, namely remembering the remaining memories of certain events. Avoidance, which is avoiding something that can make him stutter. Emotional Attacks, namely feeling emotions that make him gloomy and irritable. Sensory Motor Symptoms, namely disturbances in stuttering speech and Somatic symptoms, namely symptoms that cannot be explained by medical causes. The causes found in the novel are wrong emotional training in parenting, failure, curses received and unpleasant events in the past. So that it can be explained from the causes above that it has an impact such as changes in looking at the meaning of life like, Simon who only wanted to live to hate his father, that he would not marry and have children so that one day the heir to the Duke of Hastings would die with him. In the course of his life, Simon faced his hysteria in his own way. That is by breaking all the oaths he took to take revenge against his father.